Co-simulation of Biomechanical Design for a Robotic Exoskeleton for the Lower Limb - Lugo, E.; Ponce, P.; Molina, A.; Castro, S. (Revista Mexicana de Ingenieria Biomedica, 2014)
This work shows how the co-simulation increases the advantages and decreases the drawbacks for exoskeleton design. The proposed methodology has three stages: the design of a biomechanical part, the mechanical design and the control system. For the biomechanical analysis, OpenSim® solves the muscle-skeleton system and includes models for different conditions that can be used in the design process. SolidWorks® that is applied in assistive computer design evaluates the mechanical part of the exoskeleton and Matlab® solves the control system that takes over the exoskeleton. It allows getting a personalized design which simulates the complete walking movements, covering the kinematic restrictions to achieve a natural human movement and the user limitations when they have any problem for to walk. The results show how the co-simulation is applied to complete a virtual prototype and the programs are linked hand in hand. Although conventional simulation by one program can save money and time, it cannot solve the entire exoskeleton design problem; as a result the co-simulation is an excellent option in biomechanical, mechanical and control systems that need accurate and swift results in each part of the design process.